STUDY OF HOMOGENOUS UNIVERSE DYNAMICS IN THE THEORY OF F(R) GRAVITY - Murtadho
Observations of type Ia supernovae show that the expansion of the universe is accelerated. Cosmological constant has been taken as the standard solution to explain this phenomenon. However, cosmological constant suffers from fine tuning and coincident problems. To solve the problems of the cosmological constant, several dark energy models have been proposed, such as quintessence, k-essence, and phantom. However, beside dark energy, there exist another class of possible solution for the phenomenon of cosmic acceleration, i.e. modified gravity. This approach alters the natural behaviours of gravity, to develop solution that can explain observational phenomenons, including cosmic acceleration.